Elementary School Students' Conceptual and Procedural Knowledge in Solving Fraction Problems - Magfirotin, Elis Syafa; Amir, Mohammad Faizal (UNNES JOURNAL, 2024)
Conceptual and procedural knowledge is fundamental for students to understand and solve fraction problems comprehensively. However, empirical studies indicate that elementary school students still do not have adequate conceptual and procedural knowledge in solving fraction problems. This study aimed to analyze the forms of conceptual and procedural knowledge of elementary school students in solving fraction problems. This study used a qualitative method involving 86 participants from grades four to six in one of the public elementary schools in Sidoarjo. Seven subjects were selected to represent the forms based on each aspect of conceptual and procedural knowledge of fractions. The data analysis used was descriptive analysis with data collection methods using tests, interviews, and documentation. Empirical research showed that students can successfully use conceptual and procedural knowledge of fractions in certain forms. There are three forms of conceptual knowledge of fractions: comparing, applying, and visualizing fractions. Meanwhile, there are four forms of procedural knowledge of fractions: explaining procedures, converting fractions, adding or subtracting fractions, and simplifying fractions. The results of this study have implications for educators or academics to emphasize learning by integrating forms of conceptual and procedural knowledge so that students avoid failure in solving fraction problems. Pengetahuan konseptual dan prosedural merupakan pengetahuan mendasar agar siswa dapat memahami dan memecahkan masalah pecahan secara komprehensif. Namun, berdasarkan studi empiris diindikasikan bahwa siswa sekolah dasar masih belum memiliki pengetahuan konseptual dan prosedural yang memadai dalam memecahkan masalah pecahan. Tujuan penelitian ini untuk menganalisis bentuk-bentuk pengetahuan konseptual dan prosedural siswa sekolah dasar dalam memecahkan masalah pecahan. Penelitian ini menggunakan metode kualitatif dengan melibatkan 86 partisipan siswa kelas empat sampai enam di salah satu sekolah dasar negeri di Sidoarjo. Tujuh subjek dipilih untuk mewakili bentuk-bentuk berdasarkan setiap aspek pengetahuan konseptual dan prosedural pecahan. Analisis data yang digunakan adalah analisis deskriptif dengan metode pengumpulan data menggunakan tes, wawancara dan dokumentasi. Hasil penelitian secara empiris menunjukkan siswa berhasil menggunakan pengetahuan konseptual dan prosedural pecahan dalam bentuk-bentuk tertentu. Terdapat tiga bentuk pengetahuan konseptual pecahan, yaitu: membandingkan pecahan, menerapkan pecahan, dan memvisualisasikan pecahan. Sementara, terdapat empat bentuk pengetahuan prosedural pecahan, yaitu: menjelaskan prosedur, mengkonversi pecahan, menjumlahkan atau mengurangkan pecahan, dan menyederhanakan pecahan. Hasil penelitian ini berimplikasi bagi para pendidik atau akademisi untuk menekankan pembelajaran dengan mengintegrasikan bentuk-bentuk pengetahuan konseptual dan prosedural, agar siswa terhindar dari ketidakberhasilan dalam memecahkan masalah pecahan.